The Environmentally Friendly Practices to Fight Plants’ Diseases: Scope Review - Ziad B. Al-Rawashdeh (Journal of Global Innovations in Agricultural Sciences)
Plant diseases reduce the production and affect the food security. The use of synthetic chemicals affects the environment and individual health quality. The environmentally friendly practices were found the solution to minimize the side effects of pesticides and herbicides. This review aims to investigate the impact of environmentally friendly practices on plant disease protection. The results showed that environmentally friendly practices are very effective in controlling plant diseases and the same time reducing the environmental impacts and the individual’s health. These practices were found to be effective in improving the plant product and maximizing the economic profitability of the agricultural practices. These practices will increase the sustainability of the agricultural processes. Keywords: Environmentally friendly practices, plant diseases, cultural practices, biocontrol practices, economic profitability